Uptake of influenza vaccination, awareness and its associated barriers among medical students of a University Hospital in Central Saudi Arabia - Mohammed S. Abalkhail; Mohannad S. Alzahrany; Khaled A. Alghamdi; Muath A. Alsoliman; Mosa A. Alzahrani; Badr S. Almosned; Ibrahim M. Gosadi; Shabana Tharkar (Elsevier, 2017)
Outbreaks of influenza epidemics are common but influenza vaccination is sub-optimal among the healthcare staff including the medical students. The study aims to assess the rate of vaccine uptake among medical students, its associated barriers and levels of awareness. A cross sectional study was done at a University Hospital in Saudi Arabia on 421 medical students by self administered questionnaire from February to March 2015. The immunization rate of seasonal influenza vaccine was just 20.7% in 2015, while it was 57% for cumulative of previous three-year period. The intended uptake among those offered vaccination was 68%. The significant determinants of vaccine uptake were clinical years of medical study (p < 0.05) and previous history of vaccination (p < 0.0001). The major sources influencing vaccine uptake decision were health department guidelines, medical training, social and media influence. Barriers of vaccination constituted, assumption of not being at risk of influenza (37.9%), vaccine side effects (28.9%), questioned effectiveness of the vaccine (14.5%), and inability to allocate time (11%). Knowledge levels were unsatisfactory and males scored lower (5.4 ± 1.7) than females (6.5 ± 1.4) out of total score of 9. Both knowledge and uptake of annual influenza vaccination was inadequate. Policy makers can formulate strategies with a focus on larger coverage of medical students. Keywords: Awareness, Barriers, Influenza vaccination, Medical students, Saudi Arabia, Uptake